Patient-reported mobility function and engagement in young adults with cerebral palsy: a cross-sectional sample. (1st April 2018) - Lennon, N.; Church, C.; Miller, F.
Abstract: Purpose: To describe self-reported life satisfaction and motor function of young adults with cerebral palsy (CP). Methods: A total of 57 young adults with spastic CP classified as levels I (seven), II (25), III (16), IV (nine) by the Gross Motor Function Classification System, followed from childhood by our CP clinic, returned at a mean age of 27 years two months (SD 3 years 4 months). Self-reported life satisfaction and mobility status were measured by the Pediatric Outcomes Data Collection Instrument (PODCI), Patient-Reported Outcomes Measurement Information System (PROMIS), Functional Mobility Scale (FMS) and a project questionnaire. Surgical history and childhood mobility were confirmed from medical records. Results: The Functional Mobility Scale demonstrated limited but stable mobility function from childhood to adulthood. The PROMIS and PODCI revealed limited motor function compared with a non-disabled normative reference (p < 0.05). Descriptive results showed high dependence on transportation, housing and income; although PROMIS subscales revealed satisfaction with social activities. Self-recall of childhood mobility function using the FMS correlated highly (r = 0.8; p < 0.0001) with historical records. Conclusion: Although functional mobility is limited and community independence is not fully achieved in young adults with CP, these participants maintained childhood levels of mobility function into young adulthood, were satisfied with social roles and had minimal reports of pain. Level of Evidence Level III: